The Wheat Genome - Appels, Rudi.; Eversole, Kellye; Feuillet, Catherine; Gallagher, Dusti; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This open access book provides the first comprehensive coverage of the wheat genome sequence since the publication of the draft and reference sequences for bread wheat and durum wheat. It presents an overview and all aspects of the gold standard sequence of the bread wheat genome, IWGSC RefSeq v1.0 and its subsequent improvements through 2022 (IWGSC RefSeq v2.1), as well as the sequencing of multiple elite wheat varieties, durum wheat, and ancient wheat. The book provides a broad and extensive review of the resources, tools, and methodologies available for exploiting the wheat genome sequence for crop improvement and studying fundamental questions related to the structure, function, and evolution of the wheat genome. Wheat (Tritcum aestivum L.) is the most widely grown crop in the world, contributing approximately 20 percent of total calories and more protein in human diets than any other single source. This book is useful to students, teachers, and scientists in academia and industryinterested in gaining an understanding of the wheat genome and its application as well as plant scientists generally interested in polyploid plant species.
Introduction -- IWGSC RefSeq bread wheat reference genome sequence -- Wheat genomic resources and their role in wheat research -- Wheat genome structural and functional annotation -- The wheat transcriptome and discovery of functional gene networks -- Genome-wide resource development to accelerate gene discovery and functional analysis in wheat -- Genome-editing technology applications in wheat breeding -- Wheat genetic diversity explored through genomic approaches -- Dawn of the wheat pangenome: sequencing the genomes of 10+ elite lines -- Sequencing ancient wheat to illuminate the history of domestication -- Genome sequences from diploids and wild relatives of wheat for comparative genomics and alien Introgressions -- The impact of the durum wheat genome in identifying new germplasm for breeding -- Haplotype mapping in globally diverse germplasm for genomic-assisted wheat breeding -- Genome-informed discovery of genes and association with wheat traits -- Genomic insights on global journeys of adaptive wheat genes that brought us to modern wheat -- Genomic selection in wheat utilizing the reference sequence -- Rapid cloning of disease resistance genes in wheat. .
Keywords: Plant genetics; Plant biotechnology; Agriculture; Bioinformatics; Botanical chemistry; Plant Genetics; Plant Biotechnology; Agriculture; Bioinformatics; Plant Biochemistry